The assessment of cognitive function in the German National Cohort (NAKO): associations of demographics and psychiatric symptoms with cognitive test performance - Kleineidam, Luca; Stark, Melina; Riedel-Heller, Steffi G.; Pabst, Alexander; Schmiedek, Florian; Streit, Fabian; Rietschel, Marcella; Klinger-König, Johanna; Grabe, Hans J.; Erhardt, Angelika; Gelbrich, Götz; Schmidt, Börge; et al. (The world journal of biological psychiatry, 2023)
To describe the cognitive test battery of the German National Cohort (NAKO), a population-based mega cohort of 205,000 randomly selected participants, and to examine associations with demographic variables and selected psychiatric and neurological conditions. Initial data from 96,401 participants providing data on the cognitive performance measured by a brief cognitive test battery (12-word list recall task, semantic fluency, Stroop test, digit span backwards) was examined. Test results were summarised in cognitive domain scores using exploratory and confirmatory factor analyses. Associations with sociodemographic and psychiatric factors were analysed using linear regression and generalised additive models. Cognitive test results were best represented by two domain scores reflecting memory and executive functions. Lower cognitive functions were associated with increasing age and male sex. Higher education and absence of childhood trauma were associated with better cognitive function. Moderate to severe levels of anxiety and depression, and a history of stroke, were related to lower cognitive function with a stronger effect on executive function as compared to memory. Some associations with cognition differed by German language proficiency. The NAKO cognitive test battery and the derived cognitive domain scores for memory and executive function are sensitive measures of cognition.
Online veröffentlicht: 17. Februar 2022
Gesehen am 01.07.2024